Implementasi Program IMTAQ Dalam Meningkatkan Kecerdasan Spiritual Siswa - Afiyah, Mutmainnah; Maulidi, Achmad (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Tecnological developments and current developments have a big influence on a child’s morals. Students should not only have intellectual intelligence but also have spiritual intelligence, therefor teachers play an important role in instilling morals and increasing spiritual intellegence in student. The problem raised in this researche is the implementation of the IMTAQ program implemented MA Raudlatul Ulum Bilapora Rebba Lenteng Sumenep in creasing the spiritual intelligence of case study students wich is described in three focuses, namely: 1. What is the concept and scope of implementation of the IMTAQ program in increasing the spiritual intelligence of study students case at MA Raudlatul Ulum. 2. How is the implementation of the IMTAQ program in increasing the spiritual intelligence of case study students at MA Raudlatul Ulum. 3. What are the supporting and inhibitin factors for implementing the IMTAQ program in increasing the spiritual intelligence of case study students at MA Raudlatul Ulum.The implementation of the IMTAQ program in increasing the spiritual intelligence of case study students at MA Raudlatul Ulum was conceptualized and formed with several backgrounds whose objects were the students themselves with several objectives for implementing this IMTAQ program. The results of research show that faith and devotion to student is one of the goals of implementing the IMTAQ program at MA Raudlatul Ulum by forming several activities in it which of course in every program implemented will never be protected from supporting and inhibitin factors. According to the researcher’s review, the implementation of the IMTAQ program at MA Raudlatul Ulum can make a good contribution to the students themselves and of course to those around them